Effect of dielectric constant on asphalt layers thickness based on ground penetrating radar data analysis - Vaitkus, Audrius; Kleizienė, Rita; Karbočius, Martynas (International Conference “Environmental Engineering”, 2020)
The ground penetrating radar (GPR) in roads is use to investigate the pavement structure layers thickness on network and project level, misaligned dowels and tie bar in concrete pavement, moisture and ground water level, air voids of asphalt layers, and to assure the quality control. Since, pavement layer thickness and materials properties are the key parameters for pavement bearing capacity and residual life determination the effective and reliable GPR analysis procedure is substantial for pavement management system. However, in order to determine asphalt layers thickness the dielectric constant or GPR velocity have to be known. The most common practice to determine the dielectric constant of specific pavement layer is to drill the cores at least every 1 km, as combination of destructive and non-destructive methods. The objective of this study is to investigate the effect of the dielectric constant to asphalt layers thickness determination accuracy. The dielectric constant of asphalt layers and GPR measurements were performed in the 27th pavement sections of the Test Road. The dielectric constant of asphalt layers calculated based on drilled cores data. Analysing the wearing, binder, and base layers separately and in combination. Finally, the errors of determined thicknesses of pavement layers were compared with actual thickness. To determine the dielectric constant influence to the asphalt layer thickness of road sections were investigated by drilling cores and determined the actual thickness. The dielectric constant based on core data and GPR measurements were compared.